Significance of Local Wisdom in Preparing Arabic Teaching Materials - Nurdiana, Ryan; Kumalasari, Desy; Setiawan, Cecef; Daroini, Slamet (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to explain the position of local wisdom content in Arabic teaching materials. As a language learned in the learning process (L2), few teaching materials thoroughly carry Arabic content. If we look at the reality of multicultural Indonesian society, aspects of local wisdom of the social system of Indonesian society are included in the material studied. This is an effort to integrate culture into language learning, positively impacting language learners. A point of view must be developed and used as a discourse to understand social phenomena that occur in Indonesian society, especially in the environment of pesantren and diniyah schools. Local wisdom can be viewed as a social and communicative system that produces a kind of self-organization (autopoiesis) within a culture. This research uses a qualitative approach with a descriptive analysis method where the data obtained are processed and concluded from primary, secondary, and supporting sources. The research emphasizes that local content contributes to a deeper understanding of Arabic and culture, making the learning experience more engaging and relevant for learners. In conclusion, this research underscores the importance of integrating local wisdom and cultural content into Arabic teaching materials to enrich the language learning experience and foster a deeper connection between students and the Arabic language and culture. By recognizing the significance of local content, educators can enhance the effectiveness of their teaching methods and better prepare students for authentic and meaningful communication in Arabic-speaking communities.